ANALYSIS OF DIFFERENCES AND SIMILARITIES OF ZAKAT ACCOUNTING STANDARD NO. 109 VERSUS MPSAS ZAKAT MALAYSIA - Mia Lestari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study compares Statement of Financial Accounting Standards (PSAK) No. 109 implemented in Indonesia and Malaysian Public Sector Accounting Standards (MPSAS) Zakat implemented in Malaysia. By identifying the similarities and differences between these two standards, this study can contribute to the Zakat accounting literature and offer recommendations for developing better accounting standards in both countries. Zakat, as one of the pillars of Islam, requires transparent and accountable management. PSAK 109 regulates the management of zakat, infaq, and sadaqah with a cash-based approach, while MPSAS Zakat follows accrual-based public sector accounting principles. This research will analyze the scope aspects, including recognition, measurement, presentation, and disclosure of the two standards. This comparative analysis is expected to identify opportunities to strengthen zakat management through harmonizing standards that are more relevant to the needs of each country. This research will also discuss the impact of the differences between PSAK 109 and MPSAS Zakat on transparency and accountability in Zakat management. The results of this analysis can reveal the technical and conceptual differences between the two standards and provide strategic recommendations for zakat management institutions in Indonesia and Malaysia. Thus, this research is expected to offer a new perspective regarding the harmonization of zakat accounting standards that follow sharia principles and meet the needs of society.